Evaluating the efficacy of microbial antagonists in inducing resistance, promoting growth, and providing biological control against powdery mildew in wheat - Choudaker, Kariyappa R.; Singh, Vaibhav Kumar; Kashyap, Abhijeet Shankar; Patel, Aakash V.; Sameriya, Koshal K.; Yadav, Dhananjay; Manzar, Nazia; Kamil, Deeba; Prasad, Lakshman; Saharan, M. S. (Frontiers in Microbiology, 2024)
This study evaluates the biocontrol efficacy of three bacterial strains viz.Pseudomonas fluorescens DTPF-3, Bacillus amyloliquefaciens DTBA-11, and Bacillus subtilis DTBS-5) and two fungal strains Trichoderma harzianum Pusa-5SD and Aspergillus niger An-27) antagonists, along with their combinations at varying doses (5.0, 7.5, and 10.0 gm/kg of seeds), against wheat powdery mildew. The most effective dose (10 gm/kg seeds) was further analyzed for its impact on induced resistance and plant growth promotion under greenhouse conditions. The study measured defense enzyme activities, biochemical changes, postinfection plant growth metrics. All tested microbial antagonists at 10 gm/kg significantly reduced PM severity, with B. subtilis strain DTBS-5 outperforming others in reducing PM severity and achieving the highest biocontrol efficacy. It was followed by B. amyloliquefaciens strain DTBA-11 and P. fluorescens strain DTPF-3, with the fungal antagonists showing no significant effect. Wheat crop treated with B. subtilis strain DTBS-5 exhibited substantial increases in defense-related enzyme activities and biochemicals, suggesting an induced resistance mechanism. The study found a 45% increase in POD activity, a 50% increase in CAT activity, a 30% rise in phenolic content, and a 25% increase in soluble protein content in wheat plants treated with microbial antagonists. The study underscores the effectiveness of microbial antagonists, particularly B. subtilis strain DTBS-5, in managing wheat PM through biocontrol, induced resistance, and enhanced plant growth, offering a sustainable alternative to chemical treatments.